Clinical assessment of endothelial function in heart failure with preserved ejection fraction: A meta‐analysis with meta‐regressions. (22nd May 2021) - Ambrosino, Pasquale; Papa, Antimo; Buonauro, Agostino; Mosella, Marco; Calcaterra, Ilenia; Spedicato, Giorgio Alfredo; Maniscalco, Mauro; Di Minno, Matteo Nicola Dario
Abstract: Background: Endothelial dysfunction is a key mechanism in the development of cardiac remodelling and diastolic dysfunction in heart failure with preserved ejection fraction (HFpEF). Flow‐mediated (FMD) and nitrate‐mediated dilation (NMD) are noninvasive methods to assess endothelial function. We performed a meta‐analysis evaluating the impact of HFpEF on FMD and NMD. Methods: PubMed, Web of Science, Scopus and EMBASE databases were systematically searched according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Differences were expressed as mean difference (MD) with 95% confidence intervals (95%CI). The random effects method was used. Results: A total of seven studies were included in the final analysis, 7 with data on FMD (326 HFpEF patients and 417 controls) and 3 on NMD (185 HFpEF patients and 271 controls). Compared to controls, HFpEF patients showed significantly lower FMD (MD: −1.929; 95%CI: −2.770, −1.088; P < .0001) and NMD values (MD: −2.795; 95%CI: −3.876, −1.715; P < .0001). Sensitivity analyses substantially confirmed results. Meta‐regression models showed that increasing differences in E/A ratio (Z‐score: −2.002; P = .045), E/E' ratio (Z‐score: −2.181; P = .029) and left atrial diameter (Z‐score: −1.951; P = .050) were linked to higher differences in FMD values between cases and controls. Conclusions: Impaired endothelial function can be documented in HFpEF, with the possibility of a direct association between the severity of diastolic and endothelial dysfunction. Targeting endothelial dysfunction through pharmacological and rehabilitation strategies may represent an attractive therapeutic option.